Behavioral determinants for vaccine acceptability among rurally located college students. Issue 1 (1st January 2018) - Britt, Rebecca K.; Englebert, Andrew M.
ABSTRACT: Background: College-aged adults in a rural and medically-underserved area often struggle to receive proper vaccinations due to lower socioeconomic status coupled with life demands. Objectives: The Theory of Planned Behavior (TPB) was used as the theoretical basis to explore behavioral determinants associated with vaccination uptake in the population. Methods: This study used a questionnaire distributed to college students ( n  = 208) located in a rural area to assess the effects of social and behavioral factors on vaccination uptake. Results: Attitudes and normative beliefs towards vaccination uptake were positive but were largely impacted by work demands. Perceived behavioral control did not contribute towards the intent to receive necessary vaccines. Conclusions: Researchers conducting vaccination interventions, along with physician-patient communication, need to target attitudes and subjective norms in rural and medically underserved communities to increase vaccines, particularly HPV. In addition, results showed that promoting vaccine uptake among minorities is necessary to aid in vaccine acceptability in these communities.